Kewenangan Notaris/PPAT dalam Menerima Penitipan Pembayaran Pajak Bea Perolehan Hak Atas Tanah dan Bangunan - Hidayat, Riyan (Acta Comitas : Jurnal Hukum Kenotariatan, 2019)
One of the potential sources of tax revenues that should be explored in accordance with the current economic situation and the development of the nation's development is the type of tax on land and building use permit in after abbreviated as BPHTB. In managing the Tax on land and building permit, the eligible party is the central government, but the acceptance of tax on land and building permit is largely as an income for the region. Depositing tax on land and building permit is the obligation of the taxpayer, but in fact many tax payers deposit the payment to notary /the official certifier of title deeds whereas in the authority of notary which is regulated in the amendment of law on notary, there is no one article that determines notary obligation for paying care work tax on land and building permit. The problems of this study are how the role of Notary / the official certifier of title deeds in the tax payments on land is and building use permit and how the responsibility Notary / the official certifier of title deeds in relation to the payment of on land is and building use permit’s sale and purchase. The empirical juridical legal research method is applied in this study. This study belongs to descriptive analysis by analyzing primary data and applying interview techniques for the primary data and literature review technique for the secondary data. The techniques of qualitative method are examining, analyzing, interpreting and drawing conclusion from literature review. The result of the study shows that for notary who receives the deposit payment of tax on land and building permit shall be an action undertaken to assist and facilitate the transaction process and notary public as a public officer deemed to have a better understanding of the tax payment procedure should properly assist in the execution of the tax payment but it is not entitled to charge fees for the deposit because it is not a notary’s task which only acts on the basis of her/himself. Salah satu sumber potensi prolehan pajak yang perlu digali sesuai situasi dan kondisi perekonomian serta perkembangan pembangunan bangsa sekarang ini adalah jenis Pajak Bea Perolehan Hak Atas Tanah dan Bangunan selanjutnya disingkat BPHTB. Dalam mengelola BPHTB yang berhak adalah pemerintah pusat, namun penerimaan BPHTB sebagian besar merupakan pemasukan bagi daerah. Penyetoran BPHTB merupakan kewajiban wajib pajak, namun pada kenyataanya banyak wajib pajak yang menitipkan pembayarannya kepada Notaris/PPAT padahal dalam kewenangan Notari yang diatur dalam UUJN tidak ada satupun pasal yang menentukan kewajiban Notaris untuk pekerjaan penitipan pembayaran BPHTB.Permasalahan yang dapat diangkat dalam penelitian ini adalah Bagaimana kewenangan Notaris/PPAT dalam penitipan pembayaran pajak BPHTB dan bagaimana tanggung jawab Notaris/PPAT dalam kaitannya dengan pembayaran BPHTB atas jual beli tanah dan bangunan.Penelitian ini menggunakan metode penelitian hukum yuridis empiris. Sifat penelitian deskriptif analisis dengan teknik pengumpulan data primer dengan teknik wawancara dan teknik pengumpulan data sekunder dengan cara telaah kepustakaan. Teknik analisis data dengan metode kualitatif yaitu dianalisis dengan cara mempelajari, menganalisis, menafsirkan dan menarik kesimpulan dari studi kepustakaan dan fenomena yang ada di lapangan kemudian ditarik kesimpulan Hasil peneilitian ini menunjukan bahwa Notaris yang menerima penitipan atas pembayaran BPHTB merupakan suatu tindakan yang dilakukan untuk membantu dan memperlancar proses transaksi dan Notaris sebagai pejabat umum yang dianggap lebih memahami prosedur pembayaran pajak tersebut maka sudah sepantasnya membantu dalam melaksanakan pembayaran pajak namun tidak berhak untuk memungut biaya atas penitipa tersebut karena hal itu bukan menjadi pekerjaan Notaris hanya saja bertindak atas dasar diri pribadi.